Correlation analysis between engine power and bollard pull of tugboats in Indonesia - Rachmad Tri Soelistijono; Urip Mudjiono; Catur Rakhmad Handoko; Hendro Agus Widodo; Joessianto Eko Poetro (Politeknik Pelayaran Banten, 2026)
This study aims to analyze the correlation between engine power (horsepower) and bollard pull capacity of tugboats operating in Indonesian ports. The empirical data utilized in this research was gathered from online tugboat specifications, encompassing a sample of 12 tugboats with diverse propulsion systems and engine power ratings. A correlational analysis was employed to determine the relationship between engine power and bollard pull capacity. The analytical estimates demonstrate a strong positive correlation (β = 0.0125; R2 = 0.936), indicating that 93.6% of the variation in bollard pull can be explained by variations in engine power. These findings provide precise guidance for selecting tugboats that align with the operational requirements of Indonesian ports. Furthermore, the results suggest that strategic tugboat fleet planning, based on the relationship between engine power and bollard pull, is essential for improving port operational efficiency. This study is expected to enrich the literature regarding tugboat capacity in Indonesia and contribute to port technical and operational planning. Penelitian ini bertujuan untuk menganalisis korelasi antara tenaga mesin (horsepower) dan kapasitas bollard pull pada kapal tunda (tugboat) yang beroperasi di pelabuhan-pelabuhan Indonesia. Data empiris dalam penelitian ini diperoleh dari spesifikasi teknis kapal tunda yang tersedia secara daring, mencakup sampel sebanyak 12 kapal tunda dengan berbagai jenis sistem propulsi dan daya mesin. Analisis korelasional digunakan untuk menentukan hubungan antara tenaga mesin dan kapasitas bollard pull. Estimasi analisis menunjukkan adanya korelasi positif yang sangat kuat (β = 0,0125; R2 = 0,936), yang mengindikasikan bahwa 93,6% variasi dalam bollard pull dapat dijelaskan oleh variasi daya mesin. Temuan ini memberikan panduan yang lebih akurat dalam pemilihan kapal tunda yang sesuai dengan kebutuhan operasional pelabuhan di Indonesia. Selain itu, hasil penelitian ini menyarankan perlunya perencanaan armada kapal tunda yang didasarkan pada hubungan antara daya mesin dan bollard pull guna meningkatkan efisiensi operasional pelabuhan. Penelitian ini diharapkan dapat memperkaya literatur terkait kapasitas kapal tunda di Indonesia serta berkontribusi dalam perencanaan teknis dan operasional pelabuhan.